Advances in Pulsatile Drug Delivery System: A Promising Strategy for Tailored Therapeutics in Modern Medicine- Review - Himachand, Vuyyala; Bhavya, Tummadapu; Kusuma, Uyyuri; Sriya, Prathi; Pranavi, Ravilisetty; Rao, Nagineni Sudarshan (International Journal of Pharmaceutical Investigation, 2026)
The pulsatile drug delivery system is based on a reservoir system consisting of a drug-containing effervescent core and which are coated with a swelling membrane and a polymeric coating which is insoluble but water permeable outer membrane. The swellable polymer in swelling layers induces the rupturing of outerpolymer coating. An apparatus was designed to measure simultaneously the swelling energy/force and water uptake of discs, made of polymers. It is an advanced therapeutic technique designed to optimize the drug release patterns to accompany with the body's circadian rhythm. PDDS is distinct from the conventional drug delivery system, which typically facilitate continuous and sustained release of the Drug. While PDDS are engineered to deliver drugs in a time-controlled or stimulus-induced manner, thereby matching the chronopharmacological needs of the patient. PDDS are beneficial in the management of chronic diseases that exhibits predictable patterns viz. cardiovascular diseases, asthma, arthritis, and peptic ulcers in which the symptoms are time-dependent. By releasing the drug at a precise time, it ensures that the drug's therapeutic effect aligns with the disease's activity cycle, enhancing efficacy while decreasing the side effects and the potential for drug tolerance. PDDS are of two types: Time-controlled systems and stimuli-induced systems. The time-controlled system depends on pre-programmed mechanisms like capsular, osmotic, and reservoir devices to release the drug after a specific lag time. Whereas a stimuli-induced system releases the drug in response to specific physiological or external stimuli, such as pH, temperature, enzymes, or external triggers like light. The polymers used in PDDS are Hydroxypropyl Methylcellulose (HPMC) Polyvinyl Alcohol (PVA), Sodium alginate, Poly (Lactic-co-Glycolic Acid) (PLGA), Polylactic Acid (PLA) Polyglycolic Acid (PGA). The present work is focused on the requirements, advantages, disadvantages and a review on various drugs and polymers used in the development of PDDS.
Keywords: Pulsatile drug delivery system; Swelling Membrane; Polymers; Chrono pharmacology; Circadian rhythm.